2017
DOI: 10.1016/j.jgeb.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum apelin levels and metabolic risk markers in obese women

Abstract: BackgroundAdipose tissue hormones, Adipokines, play an important role in obesity-associated complications. Apelin has recently been added to the family of adipokines. The aim of this study was to evaluate the relationship between serum apelin levels and metabolic abnormal parameters in Egyptian obese women.Materials and methodsThe study included 400 unrelated women; they were 200 obese women and 200 non- obese matched healthy women. All participants underwent clinical, anthropometric and biochemical examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
5
0
3
Order By: Relevance
“…Several studies have demonstrated a potential link of apelin with obesity. In obese women the level of serum apelin was significantly increased in comparison to healthy controls and was positively correlated with abnormal metabolic parameters (30). The same result was observed in children, where serum level of apelin was higher in obese patients than in the control group (31).…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have demonstrated a potential link of apelin with obesity. In obese women the level of serum apelin was significantly increased in comparison to healthy controls and was positively correlated with abnormal metabolic parameters (30). The same result was observed in children, where serum level of apelin was higher in obese patients than in the control group (31).…”
Section: Discussionsupporting
confidence: 66%
“…However, some data reported in literature show that APLN level is increased in obese patients suggesting that BMI is positively correlated with APLN levels [120,121]. Moreover, some authors have suggested that in obese patients APLN expression is elevated in white adipose tissue and decreased in brown adipose tissue.…”
Section: Apelin/apj Axis: Biological Rolementioning
confidence: 99%
“…При дослідженні молодих пацієнтів з ожирінням рівень апеліну в плазмі був зниженим в порівнянні зі здоровими пацієнтами, що можна певною мірою пояснити ймовірним виснаженням його компенсаторних можливостей та розвитком і тяжкістю інсулінорезистентності при ожирінні. Проте, інше дослідження показало, що рівень апеліну в плазмі був значно вищим у дітей з ожирінням порівняно з дітьми без ожиріння та надлишкової маси тіла [2,22,24]. За даними деяких авторів, апелін вважається діагностичним маркером прогнозування розвитку неалкогольної жирової хвороби печінки і позитивно корелює з окружністю талії і холестерином ліпопротеїдів низької щільності [12].…”
Section: вступunclassified
“…BO = -0,875 моделі). Окрім того, такий результат можна пояснити компенсаторними можливостями апеліну, що знаходить підтвердження в деяких дослідженнях [1,2,22,24].…”
Section: обговоренняunclassified